Determinants of Purchase Intention for Subsidized Housing in Flood-Prone Areas: Evidence from Bekasi Regency - Mochamad Afrizal Maulana; Mulfi Sandi Yuda; Yoki Muchsam; Galih Raspati (Information Technology and Science (ITScience), 2026)
The subsidized housing sector in Indonesia, implemented through the Housing Financing Liquidity Facility (FLPP) program, plays a crucial role in improving access to adequate housing for low-income households by offering affordable prices and long-term financing schemes. However, the realization of subsidized housing in Bekasi Regency has declined sharply, from 20,004 units in 2022 to 13,908 units in 2024, representing a decrease of 30.5 percent. This trend indicates a weakening of purchase intention, suggesting that affordability alone is insufficient to sustain demand. This study aims to examine the effects of subsidized housing price, perceived flood risk, infrastructure quality, and building quality on housing purchase intention within the FLPP program in Bekasi Regency. A quantitative explanatory approach was applied using primary data collected through structured questionnaires from 100 respondents consisting of residents and prospective buyers of FLPP housing. Multiple linear regression analysis was employed to assess both partial and simultaneous effects of the independent variables. The results indicate that subsidized housing price, infrastructure quality, and building quality have positive and significant effects on housing purchase intention. Conversely, perceived flood risk has a negative and significant effect, indicating that higher flood risk perceptions reduce buyers’ willingness to purchase subsidized housing. These findings suggest that purchase intention is influenced by a comprehensive evaluation of affordability, environmental safety, and physical housing conditions. Therefore, improving flood risk mitigation and infrastructure quality, alongside maintaining affordable prices, is essential for enhancing the sustainability and effectiveness of subsidized housing programs.